Seismic performance assessment of a historical masonry-infilled RC building located in the historical peninsula of Istanbul (1940s). (November 2022) - Gunes, Baris; Mangir, Atakan; Cosgun, Turgay; Sayin, Baris; Akcay, Cemil
Abstract: The current paper presents a seismic performance evaluation methodology for masonry-infilled RC buildings based on nonlinear analyses. The entire process is illustrated using a case study of a university building constructed in the 1940s. Firstly, a finite element model of the building representing its existing state was prepared based on the current seismic codes. In the second stage, the seismic performance of the building was determined by pushover analysis. Since the seismic performance of the current building was found to be inadequate, a retrofitting proposal was prepared. The model of the retrofitted building was then examined to determine the effectiveness of the proposed retrofitting techniques. The methodology presented in the study is important in seismic analysis of RC + masonry dual system buildings before and after the retrofitting practice.